Tinjauan Hukum terhadap Manipulasi Informasi Elektronik oleh Pengemudi Ojek Online (Putusan Nomor 295/Pid.Sus/2020/Pn Mlg) - Flantino Pangku; Qomarrudin Husni (Bhirawa Law Journal, 2022)
Online-based transportation was created with the aim of making it easier for someone who wants to travel or wants to order an order without having to go to a location that is very easy to order, efficient and effective. In carrying out its activities there are problems that are detrimental to the online transportation company, namely electronic data manipulation. The research entitled Legal review of electronic information manipulation by online motorcycle taxi drivers with the first objective of analyzing and knowing the decision of the District Court Number 295/Pid.Sus/2020/PN Mlg from the perspective of the criminal act of manipulating electronic information and minimizing losses caused by information manipulation problems. electronic. Second, to find out the form of legal protection for online service companies in criminal acts of electronic information manipulation by providing appropriate sanctions for perpetrators of electronic data manipulation in order to provide a deterrent effect and follow compliance with legal norms and rules in accordance with the provisions of the applicable laws in Indonesia. The research method used in writing this thesis is to use normative research methods carried out by library research. This research was conducted using secondary data obtained from the analysis of laws and regulations relating to the title of the thesis and other legal materials such as books, journals and literature. Based on the results of the study, it can be concluded first that the perpetrator was proven guilty of committing a criminal act of manipulating electronic information. The two forms of legal protection that must be given to online transportation companies have the right to get legal protection, the forms of legal protection that must be given to online transportation companies are: compensation, termination of work and punishment.